Analisis Arus Kas Operasi, Leverage, Likuiditas, Pertumbuhan Perusahaan terhadap Revaluasi Aset Tetap - Muhammad Tarzia; Hermanto Hermanto (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this study is to analyze the effect of operating cash flow, leverage, liquidity and company growth on fixed asset revaluation. In this study, there were 4 companies that met the criteria from a total observation of 46 companies with the object of research being transportation subsector companies listed on the Indonesia Stock Exchange (IDX) during the period 2014 to 2021. The results of this study indicate that the operating cash flow variable has a negative effect on revaluation. fixed assets, leverage has no effect on fixed asset revaluation. The variable liquidity has a negative effect on the revaluation of fixed assets. Taken together operating cash flow, Leverage, Liquidity and growth of the company significantly influence the revaluation of fixed assets. This research can be taken into consideration for investors and shareholders to be more careful in receiving financial statement information provided by companies in making investment decisions. For companies to be able to determine positive policies that can maintain business continuity and meet the expectations of shareholders.